The current landscape of lipoprotein(a) in calcific aortic valvular disease. (September 2021) - Hsieh, Grace; Rizk, Theresa; Berman, Adam N.; Biery, David W.; Blankstein, Ron
Abstract : Purpose of review: Calcific aortic stenosis (CAVS) is the most common form of valvular heart disease in developed countries, increasing in prevalence with the aging population. Surgical or transcatheter aortic valve replacement is the only treatment available for CAVS. However, these interventions are typically reserved for severe symptomatic aortic stenosis (AS). The purpose of this review is to summarize the recent literature in uncovering the underlying pathophysiology of CAVS in the setting of lipoprotein (a) [Lp(a)] and emerging therapies targeting Lp(a) which may help halt disease progression in CAVS. Recent findings: Pathophysiologic, epidemiological, and genetic studies over the past two decades have provided strong evidence that Lp(a) is an important mediator of calcific aortic valvular disease (CAVD). Studies suggest that Lp(a) is a key carrier of pro-calcifying oxidized phospholipids (OxPL). The metabolism of OxPL results in a pro-inflammatory state and subsequent valvular thickening and mineralization through pro-osteogenic signaling. The identification of Lp(a) as a causal mediator of CAVD has allowed for opportunities for emerging therapeutic agents which may slow the progression of CAVD (Fig. 1 ). Summary: This review summarizes the current knowledge on the association of Lp(a) with CAVD and ongoing studies of potential Lp(a)-lowering therapies. Based on the rate-limiting and causal role of Lp(a) in progression of CAVS, these therapies may represent novel pharmacotherapies in AS and inform the developing role of Lp(a) in the clinical management of CAVD.